ANALISIS STRATEGI PEMASARAN AMAL USAHA MUHAMMADIYAH BIDANG EKONOMI PADA MUHAMMADIYAH BISNIS CENTER (MBC) - Ruslaini Ruslaini (Ekonomi Islam, 2020)
This study aimed to analyze the marketing strategies implemented by the Muhammadiyah Business Center (MBC) and to find out as well as to analyze the company's internal and external factors by using SWOT analysis, namely: Strengths, Weaknesses, Opportunities, and Threats. This research was field research, the data sources were primary and secondary data which were done through interviews, observation as well as the document collected by reviewing various relevant references as the focus of the research. Furthermore, the data analysis referred to the marketing mix of the 7P concept (Product, price, place, promotion, people, process, product psychological evidence. Then the SWOT Matrix (Strengths, Weaknesses, Opportunities, Threats). The results of the study were based on the analysis that Muhammadiyah Business Center had implemented an appropriate marketing strategy by referring to the 7P marketing concept, while the results of the SWOT matrix could be drawn the conclusions based on a number of developments through consideration of internal and external factors which would be able as the benefit of the progress of the MBC. The marketing process and MBC services were conducted honestly, in moderation. The most appropriate strategy used by Muhammadiyah Business Center in order to be the choice of consumers in selling products was the formulation of SO strategies, namely strategies using strengths to take advantage of the opportunities. Keywords: Marketing management, marketing strategy and marketing mix, sharia marketing, SWOT analysis